2006
DOI: 10.1111/j.1574-6968.2005.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetratricopeptide repeats are essential for PcrH chaperone function inPseudomonas aeruginosatype III secretion

Abstract: The type III secretion system (T3SS) is a specialized apparatus evolved by Gram-negative bacteria to deliver effector proteins into host cells, thus facilitating the establishment of an infection. Effector translocation across the target cell plasma membrane is believed to occur via pores formed by at least two secreted translocator proteins, the functions of which are dependent upon customized class II T3SS chaperones. Recently, three internal tetratricopeptide repeats (TPRs) were identified in this class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 42 publications
(81 reference statements)
1
43
1
Order By: Relevance
“…This was an unexpected result, in light of mutational analysis of PcrH, which predicted that the cleft of the chaperone would be involved in binding the major translocator (PopB), whereas the convex face contained the binding site for the minor translocator (PopD) (14). This potential discrepancy, however, can be explained by the structure of the PcrH-PopD complex presented here.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…This was an unexpected result, in light of mutational analysis of PcrH, which predicted that the cleft of the chaperone would be involved in binding the major translocator (PopB), whereas the convex face contained the binding site for the minor translocator (PopD) (14). This potential discrepancy, however, can be explained by the structure of the PcrH-PopD complex presented here.…”
Section: Discussioncontrasting
confidence: 45%
“…This potential discrepancy, however, can be explained by the structure of the PcrH-PopD complex presented here. PcrH residues whose mutagenesis by Bröms et al (14) compromised expression and secretion of both PopB and PopD are shown in yellow in Fig. 5A; residues whose mutagenesis compromised expression and secretion uniquely of PopB are depicted in magenta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Class II chaperones interact with translocon proteins (589), whereas chaperones of flagellar T3S systems are referred to as class III chaperones (431). Chaperones of translocon proteins usually contain tandem tetratricopeptide repeats (TPRs), which are imperfect 34-amino-acid repeats that are also present in eukaryotic chaperones and are often involved in protein-protein interactions (57,249,427). TPRs were also identified in the T3S chaperone YscG from Yersinia spp., which binds together with its cochaperone YscE to the needle protein YscF (530) ( Table 4).…”
Section: Guides and Bodyguards-the T3s Chaperonesmentioning
confidence: 99%